Giants in the Frame: A 1964 Photo Analysis of How Malcolm X and Dr. Harry Edwards Connected Race, Religion, and Sport - Griffin, Whitney (Religions, 2023)
Racial analysis of photography in the canon is important when unpacking layers of racial discrimination, Black manhood, and the historical dynamics within social forces that create stereotypical perceptions of African American males. Race, religion, and sport allow scholars to unpack the perceived disposability of Black lives in contemporary society. In an effort to fully understand how sport and religion inform racialized experiences in Black manhood, the current paper seeks to advance theories of visual and racial culture in a particular context. Contextual analysis of a 1964 photograph of Malcolm X and Dr. Harry Edwards synthesizes the visual turn and offers insight into how race, sport, and religion collide to raise minority pride. A contextual analysis accounts for the ways in which visual materials function within broad social ecologies of Black masculinity. Implications are discussed for the role of sport and religion in continuing activism for racial equality.